2019
DOI: 10.1021/acs.jpcc.9b07058
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence as a New Indicator for Monitoring Hydroxylated Intermediates in Persulfate-Based Advanced Oxidation Processes

Abstract: The formation of hydroxylated intermediates is the first step in the persulfate-based advanced oxidation processes (AOPs) and depends directly on the oxidation degree of recalcitrant pollutants. Therefore, the monitoring of hydroxylated intermediates plays a vital role in persulfate-based AOPs for evaluating the oxidation degree and understanding the degradation mechanism. In this work, based on the attractive amplification of luminol chemiluminescence (CL) signals by hydroxylated intermediates, we developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, ESR spectroscopy was utilized to confirm the formation of the reaction oxygen species. Figure B showed the ESR signals of two radical adducts, which were ascribed to O 2 •– and • OH radicals in combination with the results from the ESR spectrum simulation . Thus, O 2 •– and • OH radicals were generated in the proposed system.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, ESR spectroscopy was utilized to confirm the formation of the reaction oxygen species. Figure B showed the ESR signals of two radical adducts, which were ascribed to O 2 •– and • OH radicals in combination with the results from the ESR spectrum simulation . Thus, O 2 •– and • OH radicals were generated in the proposed system.…”
Section: Resultsmentioning
confidence: 78%
“…It is also reported that luminol CL could be significantly enhanced in the presence of hydroxylated intermediates generated by persulfate-based advanced oxidation processes (AOPs) of 1,2-divinylbenzene (DVB). Since the emission of light found to be dependent on the oxidation efficiency of the recalcitrant pollutants, luminol CL was proposed (Figure 4) for tracking a wider range of hydroxylated intermediates generated during persulfatebased AOPs under different degradation conditions, and other relevant organic compounds [55]. It is also reported that luminol CL could be significantly enhanced in the presence of hydroxylated intermediates generated by persulfate-based advanced oxidation processes (AOPs) of 1,2-divinylbenzene (DVB).…”
Section: Direct Chemiluminescence By Luminol and Its Derivativesmentioning
confidence: 99%
“…•− , to form stable adducts with different characteristic peaks. 22 As depicted in Figure 3b, no signals were observed for SO 4…”
Section: Resultsmentioning
confidence: 89%
“…ESR experiments were carried out using DMPO or TMP as the spin-trapping reagent to provide direct evidence for the involvement of possible oxidizing species. DMPO could capture short-lived free radicals, such as SO 4 •– , • OH, and O 2 •– , to form stable adducts with different characteristic peaks . As depicted in Figure b, no signals were observed for SO 4 •– or • OH.…”
Section: Resultsmentioning
confidence: 98%